ANALISIS TENURIAL DALAM PENGEMBANGAN KESATUAN PENGELOLAAN HUTAN (KPH): STUDI KASUS KPH GEDONG WANI, PROVINSI LAMPUNG - Sylviani Sylviani; Ismatul Hakim (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2014)
Forest management can not be separated from conflicts caused by various factors such as:economy, social, ecology and local needs for farm lands. Conflicts occured between local people and migrants. The purpose of the study are: 1) to describe the history of the Forest Management Unit Area; 2) to review the development of area utilization; and 3) to analyze the impact of the use and utilization of the area. This study used Historical and Genesis Coherently Analysis through several stages. The study indicated that some parts of FMU areas are occupied by local community as farmlands, local housing, village offices, public facilities and local market. Parts of in the FMU area have been certified as private lands and a definitive village legalized by local regulation. Conflicts in forest area are due to the low intensity of management, security and protection. The study also produced a model of land use in the FMU Unit. This results is recommended for solution alternative of land conflict in the forestry sector. One alternative solution is to implement community forest or village forest or forest village that accommodate the aspirations and community dynamics without changing the status of forest area.